Estudo sobre a variável conhecimento na determinação do valor produmétrico das empresas do setor industrial de João Pessoa-PB - Dantas, Avaní Lúcia (2007)
There are many evidences that knowledge has become an economical resource as a result from the new market logic demands, associated to competitiveness, technological development and productivity administration concepts. In this context, the advanced manufacture systems have appeared, based on organizational concepts of maximum productivity administration, in which knowledge became the main productivity factor. Organizational productivity has grown along with development, and one of the principal challenges brought by that new approach was the creation of measuring tools that enable to follow-up and understand the complex events that lead to the evolution of productive knowledge interface. Thus being, this work concerns to distributing the productivity measurement processes at industrial sections in the city of João Pessoa-PB, under the evaluation perspective of organizational knowledge retained in those companies. So as to bring forth this discussion, the literature review regarded theoretical-conceptual principles of general knowledge, organizational knowledge theory and productivity metrics. The adopted strategy for the research was a case study, accomplished in three companies, with data collected through interviews. Data analysis and interpretation happened in three moments: the individual and collective analysis of the interviews, observations in the companies and crossed analysis of the data. The attainment of the objectives prescribed in the work showed the impossibility of measuring knowledge, once, despite the companies being able to accumulate knowledge, they are unable to measure or systematize it, reaching the conclusion that measurement of the productivity processes in the companies don't consider the variable " knowledge " in the determination of their metrics on productivity.